Stakeholders’ Perspectives on Mandatory Halal Certification for Micro and Small Enterprises in Indonesia’s Food and Beverage Sector - Anita Priantina (Universiti Sains Islam Malaysia, 2025)
Matric : 4201016 (FEM)